2019
DOI: 10.1177/1367006919880274
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual effects on cognitive shifting and prefrontal activations in young children

Abstract: Aims and objectives: Bilingual children constantly experience spontaneous switching between languages in everyday settings, and some researchers suggest that this experience leads to an advantage in task performance during executive function tasks. Neural processing during executive function tasks remains largely unknown, especially in young bilingual children. Methodology: Using functional near-infrared spectroscopy, this study examined whether young children who attended an immersion second-language program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…The task arrangement in this study has been developed from the HaND paradigm (Lloyd-Fox et al, 2019). It could be named the "habituation-dishabituation paradigm of DCCS task, " which differs from the task arrangement in the previous study (Moriguchi and Lertladaluck, 2020). First, this arrangement asked children to follow three rule orders during the three sessions to control learning effects.…”
Section: Dccs Taskmentioning
confidence: 99%
“…The task arrangement in this study has been developed from the HaND paradigm (Lloyd-Fox et al, 2019). It could be named the "habituation-dishabituation paradigm of DCCS task, " which differs from the task arrangement in the previous study (Moriguchi and Lertladaluck, 2020). First, this arrangement asked children to follow three rule orders during the three sessions to control learning effects.…”
Section: Dccs Taskmentioning
confidence: 99%
“…The EEG study by Barac et al (2016) demonstrated that better differentiation of the N2/ P3 waveform was associated with better discriminability of go and no-go trials of bilingual children. The fNIRS study by Moriguchi and Lertladaluck (2019) have demonstrated that the activation in the right lateral prefrontal regions was correlated with successes during the DCCS task. Still, the correlation between activated regions and the bilingual experience was not significant, calling for more extensive research on how bilingualism affects children's neural processing in the PFC.…”
Section: Neural Evidence In Young Children's Cognitive Processesmentioning
confidence: 99%
“…Early bilingual experience and its impact on executive function have been a topical issue in bilingual neuroimaging studies (Moriguchi & Lertladaluck, 2019). The experience of shifting between two languages by inhibiting irrelevant information and attending to relevant information may affect the neural functioning during task switching (Buac & Kaushanskaya, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Arredondo et al (2017) found that early bilingualism could yield significant changes to the functional organization of schoolchildren's PFC for non-verbal attentional control, especially within the left hemisphere, associated with normative language processing and bilingual language switching. While Moriguchi and Lertladaluck (2019) failed to find an association between L2 immersion time and brain function for cognitive shifting among 3-to 5-year-old bilinguals, suggesting insufficient L2 exposure may fail to influence neurocognitive plasticity, on the other hand, long-term early life bilingual exposure would influence children's cortical organization for language processing. For instance, by mid-childhood, bilingual children show greater activation in posterior temporo-parietal regions that support more automated lexical recognition, while monolinguals rely on greater activity in the left frontal regions (Arredondo et al, 2019a).…”
Section: Introductionmentioning
confidence: 94%